Occupational health and safety - Burke, Ronald J.; Clarke, Sharon, 1968-; Cooper, Cary L. (Psychological and behavioral aspects of risk series., 2011)
Workplace accidents and errors cost organizations hundreds of billions of dollars each year, and the injured workers and their families endure considerable financial and emotional suffering. It's obvious that increasing employee health and safety pays. The accumulating evidence shows that investing in occupational health and safety results in improved financial and social responsibility performance. There are extensive country differences and wide occupational differences in the incidence of accidents and errors. The International Labour Organization (ILO) estimates that every year there are 2.2 million fatal and 270 million non-fatal accidents or occupational diseases worldwide. Occupational Health and Safety looks at the research into what causes accidents and errors in the workplace. In line with other titles in the series, Occupational Health and Safety emphasizes the psychological and behavioral aspects of risk in organizations. It highlights how organizations differ in their health and safety performance, with case studies throughout and best practices. Key elements focus on: employee selection and training, fostering employee understanding, participation and engagement in health and safety matters, developing a health and safety culture at organizational and group/work unit levels, communicating and reinforcing safe workplace practices and bench-marking one's organization against the industry leaders. The contributors to this volume come from various countries, reflecting unique interest and knowledge in particular areas.